Climate Policy, Winter Season and Impact on Agriculture in the Lerma River Basin of the Mexican Plateau - BLANCO, María del Pilar LONGAR; SANTIAGO, Mijael ALTAMIRANO; DE LA TORRE RODRÍGUEZ, José Federico; GRANADOS-RAMÍREZ, Rebeca (Journal of Environmental Management and Tourism, 2020)
Climate has presented variations within time and space. Such alterations are translated in agriculture into a reduction in productivity, and in some cases into total loss of production. The purpose of this work was to interpret and integrate the predominant weather phenomena and the variations of the weather elements, specifically the “frosts”, as indicator for planning, agricultural and livestock development, forestal, and population itself through the interaction that weather has to do with each one of them. This research was held out in the of Lerma River Basin located within the Mexican plateau, which derived from its latitude and altitude conditions, has diverse weather characteristics. The methodology included bibliographic revision, consultation of available cartography, and comparative analysis of meteorological data.